A class of logarithmically completely monotonic functions - Guo, Senlin; Srivastava, H.M. (Applied mathematics letters, 2008)
The main object of this work is to give some conditions for a class of functions to be logarithmically completely monotonic. Our result is shown to be an extension of a result which was proven in the recent literature on this subject.